2018
DOI: 10.1590/0004-282x20180064
|View full text |Cite
|
Sign up to set email alerts
|

Trends and disparities in the use of cholinesterase inhibitors to treat Alzheimer’s disease dispensed by the Brazilian public health system – 2008 to 2014: a nation-wide analysis

Abstract: In light of the high cost of dementia treatment, there is legislation authorizing free distribution of cholinesterase inhibitors to those suffering from Alzheimer’s disease in Brazil. However, the existence of this free distribution does not guarantee adequate distribution. Objectives The present study aimed to investigate the trends of prescriptions and the coverage of Alzheimer’s disease treatment using cholinesterase inhibitors from public pharmacies dispensing high-cost drugs in Brazil. Methods This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
2
9
0
3
Order By: Relevance
“…20,21 AChEIs were the first pharmacological treatment approved by the US Food and Drug Administration (FDA) for AD and have been reported to be used in 10-20% of dementia patients. [22][23][24][25] The aging population usually have multiple other chronic diseases as well as behavioral and psychological symptoms of dementia (BPSD), 12,22,[26][27][28][29][30][31][32][33][34][35] resulting in the concurrent use of five or more medications or polypharmacy. 26 The exposure of 82-98% of people with dementia to polypharmacy was reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 AChEIs were the first pharmacological treatment approved by the US Food and Drug Administration (FDA) for AD and have been reported to be used in 10-20% of dementia patients. [22][23][24][25] The aging population usually have multiple other chronic diseases as well as behavioral and psychological symptoms of dementia (BPSD), 12,22,[26][27][28][29][30][31][32][33][34][35] resulting in the concurrent use of five or more medications or polypharmacy. 26 The exposure of 82-98% of people with dementia to polypharmacy was reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…As consequence, they are more likely to require emergency services, which may be associated with the shorter duration of hospitalization and higher mortality rate. Moreover, the estimated proportion of patients with dementia treated with anticholinesterase drugs in 2014 was lower in the Northeast (5.8%) and the North (2.6%) region than the national average (16.1%) 29 . However, no data about the distribution of this critical pharmacological treatment by ethnoracial groups are available, raising the question about the coverage of governmental programs to distribute this medication among diverse ethnoracial groups.…”
Section: Discussionmentioning
confidence: 91%
“…REV BRAS EPIDEMIOL 2021; 24: E210018 However, the lack of national perspective on social, economic, and clinical factors among people with AD in Brazil lead to disparities in access, coverage, and treatment 12 . For example, a recent systematic review showed that, from seven studies that identified the prevalence of clinically-assessed dementia among older adults in Brazil, six were conducted in the Southeast (states of São Paulo and Minas Gerais) and one in the Northeast (state of Bahia) regions 13 .…”
Section: Introductionmentioning
confidence: 99%